Bio-inspired routing protocols for vehicular ad-hoc networks - Bitam, Salim; Mellouk, Abdelhamid; Wiley eBooks (London : Wiley-ISTE, 2014)
Vehicular Ad-Hoc Networks (VANETs) play a key role to develop Intelligent Transportation Systems (ITS) aiming to achieve road safety and to guaranty needs of drivers and passengers, in addition to improve the transportation productivity. One of the most important challenges of this kind of networks is the data routing between VANET nodes which should be routed with high level of Quality of Service (QoS) to ensure receiving messages in the time. Then, the driver can take the appropriate decision to improve the road safety. In the literature, there are several routing protocols for VANETs which.
2.1.2.3. Cluster-based routing2.2. Quality-of-service of VANET routing; 2.2.1. Quality-of-service definition; 2.2.2. Quality-of-service criteria; 2.2.2.1. Average end-to-end delay (measured in milliseconds); 2.2.2.2. Average jitter (measured in milliseconds); 2.2.2.3. Average available bandwidth (measured in KB/s); 2.2.2.4. Packet delivery ratio; 2.2.2.5. Normalized overhead load; 2.3. VANET routing standards; 2.3.1. Dedicated short range communication; 2.3.2. Standards for wireless access in vehicular environments (WAVE); 2.3.3. VANET standards related to routing layers.
Includes bibliographical references at the end of each chapters and index.
John Wiley and Sons
Keywords: Vehicular ad hoc networks (Computer networks); Routing protocols (Computer network protocols); Automobiles; Computer networks -- Security measures; Routing protocols (Computer network protocols); Vehicular ad hoc networks (Computer networks); BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Routing protocols (Computer network protocols); Vehicular ad hoc networks (Computer networks); Electronic books